Influence of Information and Communication Technology uses on students of two Peruvian Universities in the Post-pandemic Context - Revilla Arizaca, Christian Fidel (Revista Agustina de Educación, 2024)
There is no doubt about how the Covid-19 pandemic has changed education around the world. In this context, the use of Information and Communication Technology (ICT) has been fundamental for continue delivering classes during quarantine season. Thus, this paper tries to analyze what was the use of ICT in two Peruvian universities through semi-structured interviews with 21 students who are in the last years of their careers. The preliminary results show that there were no adequate plans to deliver that kind of education, that most professors did not take advantage of these tools, and that the students experienced different difficulties in having adequate formation during virtual classes.